Effect Of Trabeculectomy On Ocular Biometry And Refractive Errors In Pediatric Glaucoma - Guirou, Nouhoum; Dembélé, Youssouf; Napo, Abdoulaye; Japhet, Théra; Coulibaly, Drissa Moriba; Dougnon, Amassagou; Tall, Aichata; Sylla, Fatoumata (European Scientific Journal, ESJ, 2021)
Background: Pediatric glaucoma triggers refractive errors by modifying the biometry of the eye. This study was conducted with the objective of estimating the short-term biometric and refractive changes prior to and post trabeculectomy in pediatric glaucoma. Material and Methods: A 12-month, descriptive, cross-sectional study was carried out from January to December 2019, using patients operated on for pediatric glaucoma. Pre- and post-operative biometric and refraction measurements were noted. Visual acuity, axial length, corneal diameter and refraction were obtained. All ethical requirements (anonymity, free, informed, and continuous consent) were satisfied. Data analysis was done using SPSS 20.0. Results: In the present study, 47 eyes of 27 patients were surgically operated upon, from January 2019 to December 2019 at CHU-IOTA. The predominant sex was male (17 patients) at 63%, giving a sex ratio (M / F) of 1.7. The mean age was 5.04 ± 4.24. Preoperatively, the mean corneal diameter, and D90 were respectively 13.83 ± 1.51 and 12.55 ± 0.99. Preoperatively, the mean axial length, and D90, were 23.87 ± 1.29 and 22.28 ± 1.07, respectively. Preoperatively and at three month, the mean myopia (n = 36), were respectively -3.13 ± 1.83 and -1.59 ± 0.97. The mean preoperative astigmatism (n = 47) and D90 were respectively, -1.59 ± 0.77 and -1.23 ± 0.57. A statistically significant relationship (p <0.05) was found to exist between the preoperative and postoperative data of the axial length, corneal diameter, and refractive errors. Conclusions: Trabeculectomy significantly exerts a short-term positive impact on the biometrics and refraction by modifying the initial measurements and diopters.